Abnormal white matter integrity as a structural endophenotype for bipolar disorder. Issue 7 (7th March 2016) - Sarıçiçek, A.; Zorlu, N.; Yalın, N.; Hıdıroğlu, C.; Çavuşoğlu, B.; Ceylan, D.; Ada, E.; Tunca, Z.; Özerdem, A.
Abstract : Background: Several lines of evidence suggest that bipolar disorder (BD) is associated with white matter (WM) pathology. Investigation of unaffected first-degree relatives of BD patients may help to distinguish structural biomarkers of genetic risk without the confounding effects of burden of illness, medication or clinical state. In the present study, we applied tract-based spatial statistics to study WM changes in patients with BD, unaffected siblings and controls. Method: A total of 27 euthymic patients with BD type I, 20 unaffected siblings of bipolar patients and 29 healthy controls who did not have any current or past diagnosis of Axis I psychiatric disorders were enrolled in the study. Results: Fractional anisotropy (FA) was significantly lower in BD patients than in the control group in the corpus callosum, fornix, bilateral superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, anterior thalamic radiation, posterior thalamic radiation, cingulum, uncinate fasciculus, superior corona radiata, anterior corona radiata and left external capsule. In region-of-interest (ROI) analyses, we found that both unaffected siblings and bipolar patients had significantly reduced FA in the left posterior thalamic radiation, the left sagittal stratum, and the fornix compared with healthy controls. Average FA for unaffected siblings was intermediate between the healthy controls and bipolar patients within these ROIs. Conclusions: Decreased FA in the fornix, left posterior thalamic radiation and left sagittal stratum in both bipolar patients and unaffected siblings may represent a potential structural endophenotype or a trait-based marker for BD.